Inner turning point in the theory of singular Perturbations - Bobochko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct the uniform asymptotics of a solution of a singularly perturbed differential equation of Liouville type with an interior turning point.